ADD1 Single Nucleotide Polymorphisms Are Associated With Essential Hypertension Among Han and Mongolian Population in Inner Mongolia Area - Zhang, Yi; Chang, Peiye; Liu, Zhiyue (Frontiers in Genetics, 2022)
Aldosterone synthase (CYP11B2) and α-adducing (ADD1) are candidate genes play key roles during Essential hypertension (EH) incidence. However, association between their genetic mutations and the risk of EH is unclear. The present study investigated specific single-nucleotide polymorphisms (SNPs) from CYP11B2 and ADD1, and their potential role as risk factors of EH based on 423 Mongolian and 410 Han people in Inner Mongolia province. In the allelic model, people with ADD1 rs2239728-A presented a 0.74-fold risk than rs2239728-C, while the ADD1 rs4961-T was associated with a 1.37-fold higher risk than allele G in Han population. Genetic model reported that rs2239728-A carrier (AA+AC) was 0.59-fold lower than CC carrier, while rs4961-G carrier (GG+GT) was 0.59-fold lower than TT carrier in dominant model. After gender adjustment, people with rs2239728-A was 0.63-fold risk than –C in EH, but rs4961-T carrier was associated with a 1.63 times higher risk than –G in females Haplotype analysis showed that GCCT was associated with essential hypertension in Han population and it was a risk factor of EH. Our identification reported novel SNPs of ADD1 with protective significance for EH among females in Chinese Han population, together with its haplotype GCCT as a risk factor of EH.